A Comprehensive Review and Perspective on Natural Sources as Dipeptidyl Peptidase-4 Inhibitors for Management of Diabetes - Sibhghatulla Shaikh; Eun-Ju Lee; Khurshid Ahmad; Syed-Sayeed Ahmad; Jeong-Ho Lim; Inho Choi (Pharmaceuticals, 2021)
Type 2 diabetes mellitus (T2DM) is an increasing global public health problem, and its prevalence is expected to rise in coming decades. Dipeptidyl peptidase-4 (DPP-4) is a therapeutic target for the management of T2DM, and its inhibitors prevent the degradation of glucose-dependent insulinotropic peptide and glucagon-like peptide 1, and thus, maintain their endogenous levels and lower blood glucose levels. Various medicinal plant extracts and isolated bioactive compounds exhibit DPP-4 inhibitory activity. In this review, we discussed different natural sources that have been shown to have anti-diabetic efficacy with a particular emphasis on DPP-4 inhibition. Furthermore, the effect of DPP-4 inhibition on pancreatic beta cell function, skeletal muscle function, and the glucose-lowering mechanisms were also discussed. We believe that scientists looking for novel compounds with therapeutic promise against T2DM will be able to develop antidiabetic drugs using these natural sources.